Somatic Embryogenesis and Plantlet Regeneration in the Carica papaya L. cv. Eksotika - Baker, Al-Shara; Rosna, Binti Mat Taha; Jamaludin, Bin Mohamad; Hashimah, Binti Elias; Asif, Khan (MDPI AG, 2020)
A highly efficient protocol for regeneration of Carica papaya L. cv. Eksotika somatic embryos from immature zygotic embryos was developed. This study was designed to overcome the obstacles in regeneration of somatic embryos from immature zygotic embryos of “Eksotika”, especially problems associated with formation of better root quality and callus formation at the base of somatic embryos. Somatic embryos were generated by incubation of immature zygotic embryos in half-strength salt Murashige and Skoog (MS) medium with full-strength vitamins supplemented with 7.5 mg L−1 2,4-D, 100 mg L−1 L-glutamine, 50 mg L−1 myo-inositol, 45 mg L−1 adenine sulphate, 0.33% gelrite, and 6% sucrose, followed by transfer to maturation medium consisting of ½ MS medium supplemented with 5 mg L−1 phloroglucinol, 100 mg L−1 L-glutamine, 100 mg L−1 myoinositol, 68 mg L−1 adenine sulphate, 0.38% gelrite, and 3% sucrose. After that, well-formed somatic embryos were transferred to MS medium containing 3% sucrose and 0.8% agar for shoot production. The embryos were elongated in MS medium supplemented with 1 mg L−1 gibberellic acid, 0.5 mg L−1 indole-3-butyric acid, 100 mg L−1 myo-inositol, and 3.76 mg L−1 riboflavin. Root regeneration was achieved on MS medium containing 7.9 mg L−1 phloroglucinol and supported with vermiculite after 4 days of cultivation on ½ MS medium with 2 mg L−1 indole-3-butyric acid. After the rooting phase, in vitro plantlets were acclimatized in peat moss soil.